2001
DOI: 10.1080/09614520120066765
|View full text |Cite
|
Sign up to set email alerts
|

Scaling up the use of fodder shrubs in central Kenya

Abstract: Fodder shrubs provide great potential for increasing the income of smallholder dairy farmers. Following successful on-station and on-farm trials and considerable farmer-to-farmer dissemination in Embu District, Kenya, a project was initiated to introduce fodder shrubs to farmers across seven districts. Over a two-year period, a dissemination facilitator working through field-based partners assisted 150 farmer groups comprising 2600 farmers to establish 250 nurseries. Farmers planted an average of about 400 shr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…These groups provided channels for diffusion of information and for distribution of planting materials. Women's groups were particularly active in planting fodder shrubs (Wambugu, et al, 2001;Place et al, 2002). In addition, it was found that group performance in fodder shrub nursery production and outplanting was equally high among all types of groups, indicating that dissemination efforts should continue to link with all types of groups.…”
Section: Collective Actionmentioning
confidence: 91%
See 2 more Smart Citations
“…These groups provided channels for diffusion of information and for distribution of planting materials. Women's groups were particularly active in planting fodder shrubs (Wambugu, et al, 2001;Place et al, 2002). In addition, it was found that group performance in fodder shrub nursery production and outplanting was equally high among all types of groups, indicating that dissemination efforts should continue to link with all types of groups.…”
Section: Collective Actionmentioning
confidence: 91%
“…During 1999-2001, a project implemented through the Systemwide Livestock Program (SLP) of the Consultative Group on International Agricultural Research (CGIAR) helped farmers to plant calliandra and to a lesser extent L. trichandra and M. alba (mulberry) across seven districts of central Kenya involving 150 farmer groups with a membership of 2,600 farmers (Wambugu et al, 2001). In 2001-2002, the Smallholder Livestock Development Project (SDP) funded by DFID and led by ILRI and the Kenya Ministry of Livestock Development partnered with the SLP project in testing and promoting the adoption of herbaceous legumes such as Desmodium intortum and Desmodium incum, alongside the fodder shrubs on the same sites where SLP was operating (Mwangi and Wambugu, 2003).…”
Section: Fodder Shrub Research and Development In East Africamentioning
confidence: 99%
See 1 more Smart Citation
“…In a study on the achievements and impact of a fodder project in the central highlands of Kenya, Wambugu et al (2001) found that out of 2,600 group members involved in establishing fodder shrub nurseries, 60% were women. FHHs accounted for 15% of all planting households which is only slightly lower than the proportion of female headed households (18%) in central Kenya (Kimenye 1998).…”
Section: Women's Participation In Agroforestrymentioning
confidence: 99%
“…These practices, plotted by either the government ministries or private sector are either modification of an existing practice more novel to farmers. The aim is to conserve the drylands through increased vegetation cover, provision of fodder [4] and wood fuel, soil protection, food security as well as lessen negative effects of climate change [5,6].…”
Section: Introductionmentioning
confidence: 99%